EDUKASI GIZI SEIMBANG CEGAH ANEMIA PADA REMAJA SEKOLAH DI WILAYAH KABUPATEN BELITUNG TIMUR (Jurnal Mitra Masyarakat (JMM), 2024)
Iron nutritional anemia in school adolescent is one of the nutritional problems in adolescents that can affects health conditions and learning performances. Efforts to prevent anemia need to be carried out from an early age specifically by increasing nutritional knowledge of school adolescets. Nutrition education have been widely carried out in schools and are known to provide benefits in preventing anemia in school adolescents. A total of 94 students from 2 school aged 16-18 years have taken part in nutrition education activities at school in Belitung Timur Regency, Province of Bangka Belitung Islands. The results showed that a few of students (24.47%) had good nutritional knowledge with an average score of 60-70. After given the education, there was an increase in knowledge score by 36.2%. Prevention of anemia in school adolescents needs to be carried out on an ongoing basis and involves the role of various parties through educational activities and/or assissting program for school adolescents. It can be concluded that educational activities to prevent anemia are very important to increase the awareness, knowledge, attitudes, and practices of school adolescents in achieving optimal nutritional status and learning performances. Both male and female adolescents need to recognize and understand how to prevent anemia at the earlier time.